Immunological non-inferiority of a new fully liquid presentation of the MenACWY-CRM vaccine to the licensed vaccine: results from a randomized, controlled, observer-blind study in adolescents and young adults. Issue 1 (31st January 2022) - Díez-Domingo, Javier; Tinoco, Juan Carlos; Poder, Airi; Dinleyici, Ener Cagri; Nell, Haylene; Salamanca de la Cueva, Ignacio; Ince, Tolga; Moreira, Edson Duarte; Ahmed, Khatija; Luz, Kleber; Kovshirina, Yulia; Medina Pech, Carlos Eduardo; et al.
ABSTRACT: A fully liquid MenACWY-CRM vaccine presentation has been developed, modifying the meningococcal serogroup A (MenA) component from lyophilized to liquid. The safety and immunogenicity of the liquid presentation at the end of the intended shelf-life (aged for 24 or 30 months) were compared to the licensed lyophilized/liquid presentation. This multicenter, randomized (1:1), observer-blind, phase 2b study (NCT03433482) enrolled adolescents and young adults (age 10–40 years). In part 1, 844 participants received one dose of liquid presentation stored for approximately 24 months or licensed presentation. In part 2, 846 participants received one dose of liquid presentation stored for approximately 30 months or licensed presentation. After storage, the MenA free saccharide (FS) level was approximately 25% and O-acetylation was approximately 45%. The primary objective was to demonstrate non-inferiority of the liquid presentation to licensed presentation, as measured by human serum bactericidal assay (hSBA) geometric mean titers (GMTs) against MenA, 1-month post-vaccination. Immune responses against each vaccine serogroup were similar between groups. Between-group ratios of hSBA GMTs for MenA were 1.21 (part 1) and 1.11 (part 2), with two-sided 95% confidence interval lower limits (0.94 and 0.87, respectively) greater than the prespecified non-inferiority margin (0.5), thus meeting the primary study objective. No safety concerns were identified. Despite reduced O-acetylation of MenA and increased FS content, serogroup-specific immune responses induced by the fully liquid presentation were similar to those induced by the licensed MenACWY-CRM vaccine, with non-inferior anti-MenA responses. The safety profiles of the vaccine presentations were similar.